Mapping Priority Setting in Health in 17 Countries Across Asia, Latin America, and sub-Saharan Africa. Issue 1 (2nd January 2016) - Li, Ryan; Hernandez-Villafuerte, Karla; Towse, Adrian; Vlad, Ioana; Chalkidou, Kalipso
Abstract : Abstract —As more low- and middle-income countries (LMICs) commit to universal health coverage (UHC), there is a growing need for rational priority setting using health technology assessment (HTA) and other policy tools. We describe an approach for rapidly mapping LMICs' capacity and needs for rational priority setting, aimed at identifying candidate countries where technical assistance would be most viable, and present our findings from applying this approach to three continents. Drawing on the multiple streams theory and a conceptual model of HTA in health systems, we developed qualitative and quantitative indicators for political commitment, current position along UHC journey, institutional and technical capacity, health system financing characteristics, and potential economies of scale in rational priority setting and associated data collection tools. We additionally defined criteria for shortlisting countries, emphasizing feasibility of technical assistance. We purposively sampled 17 countries and gathered data up to May 2014 from various sources and applied the shortlisting criteria to these countries. The four shortlisted countries (Indonesia, Myanmar, South Africa, Ghana) had varying capacities for rational priority setting and shared clear demand for rational priority setting as a means of achieving UHC. Indonesia was the strongest candidate for technical assistance, given the potential scale of impact on its large population and potential lessons for LMICs transitioning from aid. We conducted additional in-country scoping, and technical assistance to support HTA development in Indonesia is now underway. Our approach is of potential value to development funders and initiatives seeking to maximize the impact of their aid investments in support of UHC.